2013
DOI: 10.5539/elt.v6n3p20
|View full text |Cite
|
Sign up to set email alerts
|

Language Anxiety among Gifted Learners in Malaysia

Abstract: Language anxiety has significantly sparked great concern in the second and foreign language learning world. Researches have found negative correlation between language anxiety and academic achievement of English language learners; and, most of the studies focus on average school students and tertiary level students. This paper, however, explores gifted learners' English language anxiety in ESL setting, by surveying 119 gifted learners of PERMATApintar National Gifted Center (PpNGC), Universiti Kebangsaan Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
0
18
0
2
Order By: Relevance
“…Saito et al (1996) argued that the level of the anxiety which the students experience in the beginner, intermediate and advanced level has a negative correlation with the grades which the students obtain in the exams. Kamarulzaman et al (2013) investigated the correlation between anxiety and the performance among gifted learners in Malaysia and the result revealed that anxiety correlates negatively with gifted learners' performance.…”
Section: Foreign Language Anxiety and Academic Achievementmentioning
confidence: 99%
See 2 more Smart Citations
“…Saito et al (1996) argued that the level of the anxiety which the students experience in the beginner, intermediate and advanced level has a negative correlation with the grades which the students obtain in the exams. Kamarulzaman et al (2013) investigated the correlation between anxiety and the performance among gifted learners in Malaysia and the result revealed that anxiety correlates negatively with gifted learners' performance.…”
Section: Foreign Language Anxiety and Academic Achievementmentioning
confidence: 99%
“…The relationship between FLA and the performance of the students has been widely examined by many scholars who agreed that foreign language anxiety affects the students' performance negatively (MacIntyre & Gardner 1991;Horwitz et al 1986;Phillips 1992;Kamarulzaman et al 2013). …”
Section: Foreign Language Anxiety and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of feeling is often associated with negative outcomes. Particularly, anxiety has long been discussed and regarded as a significant factor influencing learning performances and achievement (Kamarulzaman et al, 2013;SHEU, 2017). Sieber et al (1977) define anxiety as "a set of process having to do with awareness of the possibility of failure (by whatever subjective standard), and with attempts to resist that awareness, or to cope."…”
Section: Literature Reviewmentioning
confidence: 99%
“…(1986) mendefinisikan kebimbangan bahasa sebagai bentuk perasaan yang kompleks yang terdiri daripada persepsi kendiri, keyakinan diri, perasaan, dan tingkah laku berkaitan dengan pembelajaran bahasa di dalam kelas dan ia muncul daripada proses pembelajaran bahasa tersebut. MacIntyre & Gardner (1994) (Horwitz et, al., 1986;MacIntyre & Gardner, 1991;Mohd Hasrul et,al., 2013). Ini membawa maksud bahawa semakin tinggi kebimbangan yang dialami oleh pelajar, maka semakin rendah pencapaian atau hasil pembelajaran bahasa yang diperolehi oleh pelajar.…”
unclassified